2014
DOI: 10.1080/13598139.2014.968462
|View full text |Cite
|
Sign up to set email alerts
|

Conceptions of giftedness and expertise put to the empirical test

Abstract: Recent handbooks of giftedness or expertise propose a plethora of conceptions on the development of excellent performance but, to our knowledge, there are no comparative studies that provide empirical evidence of their validity to guide researchers and practitioners in their adoption of a particular conception. This study sought to close that gap by conducting an empirical comparison of the major approaches to giftedness and expertise currently in use: the IQ model, the performance model, the moderator model, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 60 publications
0
8
0
1
Order By: Relevance
“…However, the empirical basis of ELC to date evinces five blind spots we seek to address in a series of three studies. First, with regard to alternative theories of talent development in the academic domain, it has yet to be shown that ELC add incremental value over IQ, which is, besides prior achievements, the most frequently used measure to predict academic achievements . This will be the main objective of study 1.…”
Section: The Aim Of Our Current Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the empirical basis of ELC to date evinces five blind spots we seek to address in a series of three studies. First, with regard to alternative theories of talent development in the academic domain, it has yet to be shown that ELC add incremental value over IQ, which is, besides prior achievements, the most frequently used measure to predict academic achievements . This will be the main objective of study 1.…”
Section: The Aim Of Our Current Researchmentioning
confidence: 99%
“…First, with regard to alternative theories of talent development in the academic domain, it has yet to be shown that ELC add incremental value over IQ, which is, besides prior achievements, the most frequently used measure to predict academic achievements. 16 This will be the main objective of study 1. Second, most studies have been conducted in the academic domain, such as the school and university settings.…”
Section: The Aim Of Our Current Researchmentioning
confidence: 99%
“…The concept 'excellence' is socially constructed and related to general notions of students, learning and teaching (Dai & Chen, 2013). Researchers differ on conceptualizations of talent, giftedness and explanations of outstanding performances (Harder et al, 2014;Ambrose, 2010in: Laine et al, 2016. Authors such as Matthews and Foster (2006), Johnson (2005) and Dai and Chen (2013) introduce paradigms of giftedness.…”
Section: Culture Of Excellencementioning
confidence: 99%
“…In the field of giftedness research, a plethora of conceptual models and definitions of giftedness have been proposed (Harder, Vialle, & Ziegler, ; Subotnik, Olszewski‐Kubilius, & Worrell, ). Despite their differences, most contemporary models are developmental and contextual in nature, asserting that outstanding ability in a particular domain may gradually develop into outstanding talent (e.g., achievement, eminence), depending on contextual influences, including appropriate instruction and coaching, and personal influences, such as personality, motivational and psychosocial characteristics (Al‐Shabatat, ; Gagné, ; Harder et al., ; Subotnik et al., ). Also, although contemporary models acknowledge different domains of giftedness (e.g., artistic, leadership), intellectual giftedness has been the most studied domain (Jarosewich, Pfeiffer, & Morris, ).…”
Section: Introductionmentioning
confidence: 99%